2011
DOI: 10.1007/s12185-011-0820-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of subcategory and severity of chronic graft-versus-host disease evaluated by National Institutes of Health consensus criteria

Abstract: To evaluate the clinical significance of subcategory and severity of chronic graft-versus-host disease (GVHD) as defined by the National Institutes of Health (NIH) consensus criteria, we retrospectively studied 211 patients with hematologic neoplasms who survived beyond 100 days after allogeneic hematopoietic cell transplantation. Endpoints included chronic GVHD-specific survival (cGSS), duration of immunosuppressive treatment, and non-relapse mortality (NRM). A total of 96 patients fulfilled the NIH diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Furthermore, patients with severe cGVHD had a significantly higher TRM compared with patients with mild or moderate cGVHD. Our data are in accordance with recent studies that reported a correlation between cGVHD severity and outcome after allo-SCT and it is suggested that patients with severe cGVHD represent an unfavorable subgroup [3,11,18,27,38,55,56,[58][59][60][61][62]66,67].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, patients with severe cGVHD had a significantly higher TRM compared with patients with mild or moderate cGVHD. Our data are in accordance with recent studies that reported a correlation between cGVHD severity and outcome after allo-SCT and it is suggested that patients with severe cGVHD represent an unfavorable subgroup [3,11,18,27,38,55,56,[58][59][60][61][62]66,67].…”
Section: Discussionsupporting
confidence: 93%
“…First, in this study, acute and chronic GVHD were diagnosed on the basis of traditional criteria, whereas chronic GVHD was diagnosed and classified on the basis of NIH criteria in recent studies. [36][37][38][39] Therefore, our results cannot be compared with those reported in other studies. In addition, it is possible that late onset acute GVHD was classified as chronic GVHD or early onset of chronic GVHD was defined as acute GVHD.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, the severe cGVHD group was associated with lower OS and GSS than those with mild or moderate grade of cGVHD. Similarly, many previous retrospective and prospective studies have shown that severe cGVHD is associated with lower OS or GSS and higher nonrelapse mortality [5,[14][15][16][17][18]. Therefore, severe cGVHD can be a poor prognostic factor correlating well with long-term outcomes.…”
Section: Discussionmentioning
confidence: 83%